(untitled) (Journal of Geography and Environmental Management, 2017)
Research of solid waste (SWM) is relevant under one of the goals of the "Concept of transition of the Republic of Kazakhstan to the "green economy"- improving the efficiency, safety, environmental and social acceptability of a range of services for the collection, transportation, recycling, processing and disposal of municipal solid waste, increasing the share of recycling of solid waste, as well as ensuring the safe disposal of waste. Today, there are a number of ways of storage and processing of solid waste, among them the most common use in this country got the technology of landfill disposal of waste, since a significant number of them without sorting falls on authorized and unauthorized landfills, whose number is constantly growing.In suburban buffer Almaty area in recent decades, the majority of generated landfill in the study area have arisen spontaneously, and, as a result, represent the real and potential environmental hazard to the environment. To avoid future ecological catastrophe on a regional scale should pay more attention to monitoring and subsequent reclamation of authorized and unauthorized SWM disposal sites. The results of the research within the project 2006/GF4 "Development of the economic mechanism of solving the problem of pollution buffer zones city`s municipal solid waste (on examle of Almaty)" held in 2015. One of the objectives of this year is the analysis of Kapacagaypoligon MSW and several other small polygons to assess their impact on ecosystem. Study the dynamics of polygons performed by remote sensing and GIS programs.